Recovering from Maastricht - Agnès Bénassy-Quéré (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2020)
The euro area crisis was less a crisis of the euro than a crisis of the Maastricht doctrine. The latter was based on a triple ban: no monetization of fiscal deficits, no bail-out, no sovereign default. The euro architecture was also based on a strict division of tasks: the European Central Bank would stabilize prices in the euro area as a whole, whereas national governments would stabilize their own economies in case of idiosyncratic shocks. To make things even more dysfunctional, bank supervision remained under the competence of the member states. Although much has been done since the crisis to reform the Maastricht framework, there are still major flaws that weaken the single currency.
Keywords: E42; E61; F45; 330; Economic and Monetary Union; economic governance; economic convergence